Using MEMo to Discover Mutual Exclusivity Modules in Cancer. Issue 1 (1st March 2013) - Ciriello, Giovanni; Cerami, Ethan; Aksoy, Bulent Arman; Sander, Chris; Schultz, Nikolaus
Abstract: Although individual tumors show surprisingly diverse genomic alterations, these events tend to occur in a limited number of pathways, and alterations that affect the same pathway tend to not co‐occur in the same patient. While pathway analysis has been a powerful tool in cancer genomics, our knowledge of oncogenic pathway modules is incomplete. To systematically identify such modules, we have developed a novel method, Mutual Exclusivity Modules in Cancer (MEMo). The method searches and identifies modules characterized by three properties: (1) member genes are recurrently altered across a set of tumor samples; (2) member genes are known to or are likely to participate in the same biological process; and (3) alteration events within the modules are mutually exclusive. MEMo integrates multiple data types and maps genomic alterations to biological pathways. MEMo's mutual exclusivity uses a statistical model that preserves the number of alterations per gene and per sample. The MEMo software, source code and sample data sets are available for download at: http://cbio.mskcc.org/memo . Curr. Protoc. Bioinform . 41:8.17.1‐8.17.12. © 2013 by John Wiley & Sons, Inc.